Characterization of four isolates of Indian citrus ringspot virus - Y.S. AHLAWAT, N.V. HOA and (Indian Phytopathology, 2004)
The 1283 nucleotides of coat protein of four isolates of Indian Citrus Ringspot Virus, ICRSV-Dl, ICRSV-Ab, ICRSV-Ah and ICRSV-Pu have been cloned in pGEM-T easy vector and sequenced. Analysis of nucleotide and deduced amino acid sequences have shown variation near the N terminus and conservation in the core region. Sequence analysis and the phylogenic tree of both nucleotide and amino acid sequences showed that isolates ICRSV-Ab and ICRSV-Dl shared close relationship with ICRSV-D - an isolate from Delhi sequenced earlier and formed one cluster, while isolates ICRSV-Ah and ICRSV-Pu formed another cluster, and were considered as different strains of the virus. The information on ICRSV coat protein gene will be useful in developing pathogen mediated resistance.